KELOLA SAMPAH, BANGUN EKONOMI: SEJAHTERAKAN MASYARAKAT DENGAN BANK SAMPAH - Sholikhah, Ummi; Nur , Khofifah Indra Swari; Putri , Amelia Fahreza; Hartanti , Diah Widhi; Hunusalela , Merlyan Anggraeni; Zaman , Raihan Badruz; Azizah, Hani Nur; Ramadhani , Rifki Fahrisal; Nasution , Jelita Putri Afdilla; Safitri , Rizka Ayu; Zaidan , Muhadzdzib Dzaky; Agustin , Rahmawati Aulia; Shafiyah , Salsabilatus (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2025)
A waste bank is a place for sorting and collecting waste that can be recycled or has economic value. The waste bank in Kraton Village functions to manage community waste. However, waste management in Kraton Village was stopped due to the Covid pandemic in 2022. The cessation of the waste bank's duties resulted in a buildup of waste at the waste bank's base camp. Therefore, efforts are needed to reactivate the Kraton Village waste bank program to realize better waste management. This effort was carried out in stages over approximately five weeks. The results of this activity began to be seen in the second stage, namely assistance from the Kraton Village waste bank. This series of activities resulted in the regeneration of the Kraton Village waste bank to be better and of maximum benefit. This is proven by the reduction in waste accumulation and waste management as a job that can become an economic field for village communities.